Distributed energy resources and energy communities: exploring a systems engineering view of an emerging phenomenon - Hansen, P; Barnes, J (NEWCOMERS project, 2021)
This working paper is part of Work Package 4 of the NEWCOMERS project and explores the interface of two popular concepts in energy transition discourse: distributed energy resources (DERs) and energy communities (ECs). DERs are expected to play an increasingly prominent role in the creation and operation of decarbonised and decentralised energy systems. ECs have been proposed, by the European Commission amongst others, as holding the potential to empower energy consumers, making them active participants in energy systems who use, own and manage DERs. On the surface, ECs appear to be well positioned to develop DERs in the realisation of decentralised and decarbonised energy futures. This working paper examines and ultimately challenges this assumption. To take a closer look at contemporary EC activity, the paper first clarifies what DERs are conceptually, and then applies this understanding to the 10 NEWCOMER ECs to assess the extent to which they employ DERs within their current and potential future operation.